Human Umbilical Cord Mesenchymal Stem Cell Differentiation Into Odontoblast-Like Cells and Endothelial Cells: A Potential Cell Source for Dental Pulp Tissue Engineering - Zhang, Shuang; Zhang, Weiwei; Li, Yanping; Ren, Liping; Deng, Haotian; Yin, Xiaowei; Gao, Xu; Pan, Shuang; Niu, Yumei (Frontiers in Physiology, 2020)
Objectives: Dental pulp regeneration is considered an ideal approach for treating dental pulp disease. Because pulp is composed of various cells , determining the proper seed cells is critical. We explored the potential of human umbilical cord mesenchymal stem cells(hUCMSCs) as seed cells for dental pulp regeneration. Materials and Methods:Liquid extract of human treated dentin matrix(LE-TDM) was acquired to culture hUCMSCs. Odontoblast-specific markers were detected by Western blot, qRT-PCR and immunofluorescence assays. Endothelial differentiation of hUCMSCs was examined according to VEGF induction by Western blot, qRT-PCR and Matrigel assays. hUCMSCs and VEGF-induced hUCMSCs (V-hUCMSCs) were also cocultured in vivo for the Matrigel plug assay and in vitro for RNA-sequencing (RNAseq). Last, encapsulated mono-cultured hUCMSCs or cocultured hUCMSCs and VhUCMSCs in scaffolds were injected into the root segments, and transplanted into immunodeficient mice for dental pulp regeneration. Results: Under LE-TDM induction, hUCMSCs expressed specific odontoblasts markers (DSPP, DMP-1, DSP). Under VEGF induction, hUCMSCs expressed functional endothelial markers (CD31, eNOs, vWF). In vivo, the Matrigel plug assay indicated that cocultured hUCMSCs and V-hUCMSCs, formed extensive vessel-like structures. RNA-seq result indicated that cocultured V-hUCMSCs exhibited high Hif-1 signaling pathway activity. Both the hUCMSCs mono-culture and cculture groups showed pulp-like tissue regeneration.The cocultured group showed more extracellular matrix and vascularization than the mono-cultured group in vivo. Conclusions: hUCMSCs can differentiate into odontoblast-like cells and functional endothelial cells. Cocultured hUCMSCs and V-hUCMSCs formed vessel-like structure and regenerated dental pulp-like tissue. Therefore, hUCMSCs may be used an alternative seed cell source for angiogenesis and dental pulp regeneration .